Pengaruh Penanaman Modal Dalam Negeri Penanaman Modal Asing dan Infrastruktur Transportasi Terhadap Pertumbuhan Ekonomi - Novira Putri Ayunda; Yollit Permata Sari (Jurnal Kajian Ekonomi dan Pembangunan, 2021)
This study aims to determine the effect of domestic investment, foreign investment and transportation infrastructure on economic growth in Indonesia. This type of research is quantitative research. The data used are secondary data from 1980 to 2019 collected through documentation and related agencies. . This study uses multiple linear regression analysis and Error Correction Model (ECM). The results of this study indicate that: (1) domestic investment has no significant effect on economic growth in Indonesia; (2) foreign investment has a significant effect in increasing economic growth in Indonesia; (3) Transportation infrastructure has a significant effect in increasing economic growth in Indonesia.